Effect of Firm Size, Profitability, Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Allowance for Impairment Losses (CKPN) on Earnings Management (Study on Regional Development Banks in Indonesia 2018-2022) - ginting, rafles (Department of Accounting-Faculty of Economic and Business (FEB), 2023)
The financial report contains information regarding the company's economic performance—flexibility in applying accounting methods that create opportunities for management to influence earnings. The purpose of this study was to determine the effect of Firm Size (Total Assets), Profitability (ROA), Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Allowance for impairment losses (CKPN) on Earnings Management (Discretionary Accruals Jones modified model) study on Regional Development Banks in Indonesia 2018-2022. The study used a purposive sampling technique, so the sample was 24 conventional BPD from 26 BPD in Indonesia. The data used is pooled data with a total of 120 observations. The analytical method used is the multiple regression analysis methods. The results showed that Total Assets, CAR, NPL and CKPN partially did not affect earnings management, while ROA had a positive and significant impact. Simultaneously these five variables affect earnings management in Regional Development Banks.